Political Rituals and Popular Politicization in Imperial Brazil (Almanack, 2022)
This article compares the mechanisms of popular politicization innineteenth-century France and Brazil, in light of the innovative approachesof Emmanuel Fureix, presented at Almanack’s forum on 26 August 2014,and published as an article in this issue. Fureix analyzes rites of protestin France from the 1820s to the 1840s and suggests that oppositionfunerals, political banquets, and charivaris were part of a process of predemocraticpoliticization. Although it is easy to identify similar practicesin nineteenth-century Brazil, they did not lead to a more democratic or“modern” politics in the second half of the century.